Application of Several Forecasting Method on Refined Sugar Production at PT. Perkebunan Nusantara X - Damanik , Immanuel; Gunadya , Ida Bagus Putu; Aviantara , I Gusti Ngurah Apriadi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Forecasting is the process of making a future prediction based on the present and past data using trend analysis. The purpose of this study was(1) to know historical pattern of refined sugar production, (2) to know what are the forecasting models that be used for prediction, (3) to get the best forecasting model by using accuracy test. This study use secondary data from PT Perkebunan Nusantara X and processing data by using Microsoft Excel. Based on analysis results exponential smoothing by using α = 0.8 is the best model. As comparison by using moving average with 2 period and double exponential smoothing with α = 0.6. The accuracy test of exponential smoothing α = 0.8 showing with value MAD = 2, MSE = 9, and MAPE = 36%. On validity test of forecasting models, exponential smoothing had showing value MAD = 1,025, MSE = 2,113,927, MAPE = 22%. Results of forecasting production with 6 period on the future is R1 = 5,106, R2 =5,047, R3 = 5,035, R4 = 5,032, R5 = 5,032, R6 = 5,032.